2018
DOI: 10.1063/1.5012267
|View full text |Cite
|
Sign up to set email alerts
|

Spall response of single-crystal copper

Abstract: We performed a series of systematic spall experiments on single-crystal copper in an effort to determine and isolate the effects of crystal orientation, peak stress, and unloading strain rate on the tensile spall strength. Strain rates ranging from 0.62 to 2.2 × 106 s−1 and peak shock stresses in the 5–14 GPa range, with one additional experiment near 50 GPa, were explored as part of this work. Gun-driven impactors, called flyer plates, generated flat top shocks followed by spall. This work highlights the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The factor of 1/2 results from the approximation that the particle velocity is half the free-surface velocity. It is important to note that this is a simple, although widely used, approximation; it is useful for comparison between samples, assuming that any errors are systematic and similar for all experiments [11]. From the columns for peak stress and strain-rate in Table 2 it is clear that the four experiments can be grouped into two low stress and two high stress shots, with a low strain-rate and a high strain-rate example in each.…”
Section: Plate-impact Experimentsmentioning
confidence: 99%
“…The factor of 1/2 results from the approximation that the particle velocity is half the free-surface velocity. It is important to note that this is a simple, although widely used, approximation; it is useful for comparison between samples, assuming that any errors are systematic and similar for all experiments [11]. From the columns for peak stress and strain-rate in Table 2 it is clear that the four experiments can be grouped into two low stress and two high stress shots, with a low strain-rate and a high strain-rate example in each.…”
Section: Plate-impact Experimentsmentioning
confidence: 99%
“…The predictive modeling of the experimentally observed behavior of metallic materials under shock loading conditions (wave structures, spall strengths) is a critical challenge toward the design of next-generation structural materials [3]. Earlier studies revealed that spallation is a complex multi-scale process [1,4], affected by many factors such as shock pressure [5], loading waveform [6], strain rate [7,8], temperature [9,10], and heterogeneity in the microstructure [11][12][13]. Compared to the loading conditions that can be directly controlled, it is more difficult to study the effect of microstructure on spallation due to the lack of high resolution and ultra-fast in-situ diagnostic technology.…”
Section: Introductionmentioning
confidence: 99%
“…Abundant work related to damage or spallation has been successfully conducted using MD simulations [10][11][12][13][14][15]. Many factors, such as the shock intensity [16], loading rate [17], crystalline orientation [18,19], intrinsic defect [20,21] impurity [22] and grain size [23,24], have been considered.…”
Section: Introductionmentioning
confidence: 99%